Sikap dan Partisipasi Petani dalam Program Pelatihan Agribisnis Kedelai di Kabupaten Grobogan - Prasetyo, Agus Subhan; Gayatri, Siwi; Satmoko, Sriroso (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2021)
Farmers' welfare is the central point of agricultural development. Nevertheless, farmers still have many problems. One of the solutions from the government is through farmer empowerment programs. It aims to increase the knowledge, attitudes, and skills of farmers to develop more productive farming. Proper farmers' attitudes and participation in supporting the program are required. Therefore, this research was conducted to analyze the attitude and participation of farmers in the soybean agribusiness training program in the Grobogan Regency. The research used a case study method. The technique of determining respondents used the census method. Respondents to the research were 109 farmers who participated in the soybean agribusiness training program. The data was collected by using a questionnaire, interview, observation, and literature study. Descriptive analysis and the Likert scale were used to analyze the data. Overall, the research results showed that the attitude of farmers to the soybean agribusiness training program is in a "good" category. The attitude of farmers in the soybean agribusiness training program was seen from three indicators, 1) cognitive, 2) affective, and 3) psychomotor. In addition, the participation of farmers in soybean agribusiness training programs has been maximized and is classified in the high category. This condition showed that farmers were active in the implementation of soybean agribusiness training programs. Farmers were not only active in asking questions but actively giving opinions based on their experiences. So that farmers were able to understand and applied the material that the facilitator had given.Kesejahteraan petani merupakan titik sentral pembangunan pertanian. Namun pada kenyataannya petani masih memiliki banyak masalah. Salah satu solusi dari pemerintah adalah melalui program pemberdayaan petani. Hal ini bertujuan untuk meningkatkan pengetahuan, sikap, dan keterampilan para petani sehingga dapat mengembangkan usaha tani yang lebih produktif. Untuk mendukung program tersebut diperlukan sikap dan partisipasi yang tinggi dari petani. Oleh karena itu, penelitian ini dilakukan dengan tujuan untuk menganalisis sikap dan partisipasi petani dalam program pelatihan agribisnis kedelai di Kabupaten Grobogan. Penelitian ini menggunakan metode studi kasus. Teknik penentuan responden menggunakan metode sensus. Responden penelitian ini adalah 109 petani yang mengikuti program pelatihan agribisnis kedelai. Pengumpulan data dilakukan dengan menggunakan kuesioner, wawancara, observasi dan studi kepustakaan. Analisis deskriptif dan skala likert digunakan untuk menganalisis data. Hasil penelitian menunjukkan bahwa sikap petani terhadap program pelatihan agribisnis kedelai berada pada kategori baik. Sikap petani dalam program pelatihan agribisnis kedelai dilihat dari tiga indikator, 1) kognitif, 2) afektif, dan 3) psikomotorik. Selain itu, partisipasi petani dalam program pelatihan agribisnis kedelai sudah maksimal dan tergolong dalam kategori tinggi. Kondisi ini menujukkan bahwa petani aktif dalam pelaksanaan program pelatihan agribisnis kedelai. Keaktifan petani bukan hanya bertanya melainkan aktif memberikan pendapat berdasarkan pengalaman yang dimiliki. Sehingga menjadikan petani mampu memahami dan menerapkan materi yang telah diberikan oleh fasilitator